Oportunidades de mejora para la fase de ejecución de proyectos de inversión pública de la función salud, en el Gobierno Regional Piura, entre los años 2018-2021 - Hidalgo León, Manuel Leonidas (2023)
The present research work identifies various improvement opportunities for the execution phase of health investment projects managed by the Piura Regional Government. It addresses the study of cases of six projects in the execution phase; from there on, design and implementation limitations of the investment policy are identified. The research used a qualitative investigation method, which employs instruments such as interviews and field cards. Furthermore, to explore lessons learned in the management of public investment systems in Latin America; useful for proposing opportunities for improvement. Regarding the limitations of the design of the investment policy, it is found that the control and incentive mechanisms were not contemplated in the original design of the policy and that their subsequent incorporation slows down the execution; in addition, of not noticing, during the design, the complexity of the formal policy in the practice. The execution limitations concern the inadequate institutional performance implementing the public investment policy, where disorganized human resources; weak ability for coordination; moreover, to a disorderly evolution of public investment policy are noticeable. The opportunities for improvement concern design issues such as: instrumentalizing the investment policy; enhance supervision and control and promote incentives with clear rules and goals. For execution issues, it is necessary to prepare the organization for investment challenges; strengthen or develop capacities for a better management of investment projects and promote the special field in investment projects for the health departmen